Electrochemical Carbon Dioxide Reduction to Ethylene: From Mechanistic Understanding to Catalyst Surface Engineering - Junpeng Qu; Xianjun Cao; Li Gao; Jiayi Li; Lu Li; Yuhan Xie; Yufei Zhao; Jinqiang Zhang; Minghong Wu; Hao Liu (Nano-Micro Letters, 2023)
Highlights Three key processes in carbon dioxide reduction reaction (CO2RR) for ethylene generation were discussed, including CO2 adsorption/activation, *CO intermediates formation, and C-C coupling. The preferable mechanism for ethylene over C1 and other C2 products reaction pathways. Engineering strategies of Cu-based catalysts for CO2RR-ethylene.